Metal-Free Quantum Dots-Based Nanomaterials for Biosensors - Bilgin Simsek, Esra (Wiley, 2023)
Quantum dots (QDs) have gained particular interest owing to their optical, electrochemical, and structural features. Especially, photochemical and florescence features of QDs provide them a favorable platform for sensing areas. These zero-dimensional materials can considerably improve the analytical abilities of sensors, such as limit of detection and sensitivity. However, traditional metal-based QDs have drawbacks such as harmfulness and non-biodegradability, so it is essential to explore metal-free QDs. Carbonaceous QDs, namely carbon QDs (CQDs), graphene QDs (GQDs), and graphitic carbon nitride (CNQDs) QDs have been newly discovered quantum-sized materials biosensing and detection applications owing to their excellent photostability, harmless, biocompatibility, and unique quantum features. In this report, recent progress on the preparation of metal-free quantum sized sensors such as CQDs, GQDs and CNQDs was investigated. The optical and electrochemical techniques employed to determine the bioanalytes were reported by comparing linear concentration range and detection limits. The aim is to guide future investigations into metal-free and safer biosensor design via developing CQD-, GQD-, and CNQD-based biosensors. © 2023 Elsevier B.V., All rights reserved.
Keywords: Biosensor; CQDs; g-C3N4; GQDs; metal-free; quantum dot